2014
DOI: 10.1371/journal.pone.0110726
|View full text |Cite
|
Sign up to set email alerts
|

MacSyFinder: A Program to Mine Genomes for Molecular Systems with an Application to CRISPR-Cas Systems

Abstract: MotivationBiologists often wish to use their knowledge on a few experimental models of a given molecular system to identify homologs in genomic data. We developed a generic tool for this purpose.Results Macromolecular System Finder (MacSyFinder) provides a flexible framework to model the properties of molecular systems (cellular machinery or pathway) including their components, evolutionary associations with other systems and genetic architecture. Modelled features also include functional analogs, and the mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
324
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 334 publications
(327 citation statements)
references
References 27 publications
1
324
0
2
Order By: Relevance
“…Clusters of cas genes were identified and classified using MacSyFinder (Abby et al , 2014). CRISPR arrays were identified following a previously published methodology (Touchon et al , 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Clusters of cas genes were identified and classified using MacSyFinder (Abby et al , 2014). CRISPR arrays were identified following a previously published methodology (Touchon et al , 2011).…”
Section: Methodsmentioning
confidence: 99%
“…CAS elements were identified using MacSyFinder (Abby et al, 2014). Maximal E -value was set at 1.0, maximal independent E -value was 0.001, and minimal profile coverage parameters were set for CAS element identification.…”
Section: Methodsmentioning
confidence: 99%
“…macsyfinder is an excellent genome mining software program that selects a profile with the highest score when facing a potential Cas protein with multiple profiles. It is therefore challenging for this program to pick the accurate profiles for multidomain proteins, such as the fused Cas protein, in which multiprofiles match the same target sequence.…”
Section: Resultsmentioning
confidence: 99%
“…The three methods (CasLocusAnno, Makarova et al and MACSYFINDER) identified 8447, 9327 and 7939 Cas proteins in all cas loci, respectively (Fig. 3C) MACSYFINDER is an excellent genome mining software program [27] that selects a profile with the highest score when facing a potential Cas protein with multiple profiles. It is therefore challenging for this program to pick the accurate profiles for multidomain proteins, Our developed web-based server, CasLocusAnno, allows users to submit data via three forms…”
Section: Cas Protein Comparison Annotated By Caslocusanno Crisprcasfmentioning
confidence: 99%